Children's Self-Regulation and School Achievement in Cultural Contexts: The Role of Maternal Restrictive Control - Weis, Mirjam; Trommsdorff, Gisela; Muñoz, Lorena (Frontiers in Psychology, 2016)
Self-regulation can be developed through parent-child interactions and has been related to developmental outcomes, e.g. such as educational achievement. This study examined cross-cultural differences and similarities in maternal restrictive control, self-regulation (i.e., behavior and emotion regulation) and school achievement and relations among these variables in Germany and Chile. Seventy-six German and 167 Chilean fourth graders, their mothers, and their teachers participated. Mothers and teachers rated children’s behavior regulation with a subscale of the Strengths and Difficulties Questionnaire. Children reported their use of emotion regulation strategies on the Questionnaire for the Measurement of Stress and Coping. Mothers rated maternal restrictive control by answering the Parenting Practice Questionnaire. School achievement was assessed by grades for language and mathematics. Results showed higher behavior regulation of German children in comparison to Chilean children and a higher preference of restrictive parental control in Chilean mothers than in German mothers. Regression analyses revealed positive relations between children’s behavior regulation and school achievement in Germany and in Chile. Further, in both cultural contexts, maternal restrictive control was related negatively to behavior regulation and positively to anger-oriented emotion regulation. In sum, the study showed the central function of behavior regulation for school achievement underlining negative relations of maternal restrictive control with children’s self-regulation and school achievement in diverse cultural contexts. Culturally adapted interventions related to parenting practices to promote children’s behavior regulation may assist in also promoting children’s school achievement.